In article <firstname.lastname@example.org>, Wouter Geelen <email@example.com> wrote:
>I tried to do this myself but I can't get it done. I got >the following equation.
>Ti = -1200*exp(-1/7200*t)+1200
>Now I want to solve this function for Ti = 1080. So what I >want to find is t. How do I do that :?
Ti = -1200*exp(-1/7200*t)+1200, so Ti - 1200 = -1200 * exp(-t/7200), so (1200 - Ti)/1200 = exp(-t/7200), so ln((1200 - Ti)/1200) = -t/7200, so -ln(1200/(1200-Ti)) = -t/7200, so t = 7200 * ln(1200/(1200-Ti))
Substituting in Ti = 1080, we get the result 7200 * ln(10) which is about 16578.61267.
-- "Is there any thing whereof it may be said, See, this is new? It hath been already of old time, which was before us." -- Ecclesiastes